Morphology and histology of the uropygial gland in Antarctic birds: relationship with their contact with the aquatic environment? - Chiale, María Cecilia (2014)
Fil: Chiale, María Cecilia. División Zoología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina